Double Slit with an Einstein–Podolsky–Rosen Pair - Bar Y. Peled; Amit Te’eni; Danko Georgiev; Eliahu Cohen; Avishy Carmi (Applied Sciences, 2020)
In this somewhat pedagogical paper we revisit complementarity relations in bipartite quantum systems. Focusing on continuous-variable systems, we examine the influential class of EPR-like states through a generalization to Gaussian states and present some new quantitative relations between entanglement and local interference within symmetric and asymmetric double-double-slit scenarios. This approach is then related to ancilla-based quantum measurements, and weak measurements in particular. Finally, we tie up the notions of distinguishability, predictability, coherence and visibility while drawing some specific connections between them.